Implementation of outcome based education in the faculty of mechanical engineering, universiti malaysia pahang : An experience - Mohd Ruzaimi, Mat Rejab; Muhamad, Mat Noor; Rahman, Md Mustafizur; Kadirgama, Kumaran; Mohd Shahrir Mohd, Sani; Ahmad Nasser, Mohd Rose; Rosli, Abu Bakar; Ahmad Syahrizan, Sulaiman (2008)
This paper was discussed about an experience of Outcome Based Education (OBE) implementation in the Faculty of Mechanical Engineering (FKM), Universiti Malaysia Pahang (UMP) since 2006. The faculty had derived and formulated its own strategy on OBE as well as teaching and learning to aid the implementation. The process of implementation involved of training the representative, planning the implementation process and formulating the outcomes. The teaching approaches which is teacher centered were modified to mix with student centered ensure that graduates attain our planned outcomes.